2009
DOI: 10.1021/ja806534r
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Mechanism of Electron Capture and Electron Transfer Dissociation Using Tags with Variable Electron Affinity

Abstract: Electron capture dissociation (ECD) and electron transfer dissociation (ETD) of doubly protonated electron affinity (EA)-tuned peptides were studied to further illuminate the mechanism of these processes. The model peptide FQpSEEQQQTEDELQDK, containing a phosphoserine residue, was converted to EA-tuned peptides via β-elimination and Michael addition of various thiol compounds. These include propanyl, benzyl, 4-cyanobenzyl, perfluorobenzyl, 3,5-dicyanobenzyl, 3-nitrobenzyl and 3,5-dinitrobenzyl structural moiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 127 publications
5
91
0
Order By: Relevance
“…The suppressed backbone bond cleavages observed following ECD of the hydrogen-deficient species is analogous to the results obtained in ECD of peptides modified with tags having high electron affinity [36], peptides derivatized with fixed charge tags [34,35], radical and hydrogen atom traps [35], nitrated peptides [37], and peptides featuring a high number of glutamic acid and asparagine residues [38]. These reports [35][36][37][38] and our results highlight the importance of the reactive aminoketyl intermediate in ECD and indicate that N-C α bond cleavages are largely quenched, or eliminated, when the formation of the reactive aminoketyl radical intermediate is inhibited.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The suppressed backbone bond cleavages observed following ECD of the hydrogen-deficient species is analogous to the results obtained in ECD of peptides modified with tags having high electron affinity [36], peptides derivatized with fixed charge tags [34,35], radical and hydrogen atom traps [35], nitrated peptides [37], and peptides featuring a high number of glutamic acid and asparagine residues [38]. These reports [35][36][37][38] and our results highlight the importance of the reactive aminoketyl intermediate in ECD and indicate that N-C α bond cleavages are largely quenched, or eliminated, when the formation of the reactive aminoketyl radical intermediate is inhibited.…”
Section: Discussionsupporting
confidence: 73%
“…ECD on peptides carrying fixed charge tags [34,35] and electron traps [36] has been performed to examine the effect of these groups on the dissociation outcome. For instance, 2,4,6-trimethylpyridinium (TMP), which was postulated to act as a radical trap and also inhibits hydrogen atom formation, was used as a fixed charge tag for two amyloid β peptides [34].…”
Section: Dissociation Of Doubly [M + H] 2+• and Triply [M + 2h] 3+mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the anion formed by the ester carbonyl requires less Coulomb stabilization than the OCN π* orbital. However, Beauchamp and co-workers [32] showed that electron capture and cleavage of amide bonds were only affected when substituent tags in the peptide had EA greater than ca. 50 kJ/mol.…”
Section: Ecd Results Are Best Explained By Different Product Stabilitiesmentioning
confidence: 99%
“…Turecek and co-workers prevented ECD backbone cleavages by the addition of a stable electron and hydrogen atom trap to peptide ions [31]. More recently, Beauchamp and co-workers inserted tags with variable electron affinities (EA; -1.15 to +1.65 eV) into a peptide sequence and analyzed the model peptides by ECD and ETD [32]. Two main conclusions were drawn.…”
Section: Introductionmentioning
confidence: 99%